Old age and elderly people: social representations of adolescent students Vejez y persona anciana: representaciones sociales de adolescentes escolares Velhice e pessoa idosa: representações sociais de adolescentes escolares - Maria Célia de Freitas; Maria Assunção Ferreira (Universidade de São Paulo, 2013)
OBJECTIVE: to know the main elements of social representations about elderly people and old age among adolescents at a public high school. METHOD: 172 adolescents between 14 and 19 years of age participated. The free evocation of words technique was applied through the terms elderly and old age. RESULTS: The main elements of the representations significantly designed for elderly people were: respect and disrespect, 78; experience, 49; care, 32; wisdom, 23; fragility, 19. For old age: disease, 51; retirement, 27; experience, 27; wisdom, 19; wrinkles, 17. The social representations of adolescents are strongly marked by physical, psychological and social aspects, with positive and negative aspects about old age. CONCLUSION: Participatory health education activities are needed to make adolescents critically reflect on and the condition of elderly people in contemporary society. OBJETIVO: Conocer los elementos centrales de las representaciones sociales de adolescentes de una institución de enseñanza media pública sobre la persona anciana y la vejez. MÉTODO: Participaron 172 adolescentes, entre 14 e 19 años. Se aplicó la técnica de evocación libre de palabras a través de los términos inductores persona anciana y vejez. RESULTADOS: Los elementos centrales de las representaciones significativamente construidos para persona anciana fueron: respeto y desacato, 78; experiencia, 49; atención, 32; sabiduría, 23; fragilidad, 19. Para vejez fueron: enfermedad, 51; jubilación, 27; experiencia, 27; sabiduría, 19; arrugas, 17. Las representaciones sociales de los adolescentes están fuertemente marcadas por aspectos físicos, psicológicos y sociales con aspectos positivos y negativos sobre la vejez. CONCLUSÍON: Se concluyó por la necesidad de realización de actividades de educación en salud participativas de manera a conducir los adolescentes a la crítica y reflexión sobre el envejecimiento y la condición del anciano en la sociedad contemporánea. OBJETIVO: conhecer os elementos centrais das representações sociais de adolescentes de uma instituição de ensino médio pública sobre a pessoa idosa e a velhice. MÉTODO: participaram 172 adolescentes, entre 14 e 19 anos. Aplicou-se a técnica de evocação livre de palavras, através dos termos indutores pessoa idosa e velhice. RESULTADOS: os elementos centrais das representações significativamente construídos para pessoa idosa foram: respeito e desrespeito, 78; experiência, 49; cuidado, 32; sabedoria, 23; fragilidade, 19. Para velhice foram: doença, 51; aposentadoria, 27; experiência, 27; sabedoria, 19; rugas, 17. As representações sociais dos adolescentes estão fortemente marcadas por aspectos físicos, psicológicos e sociais com aspectos positivos e negativos sobre a velhice. CONCLUSÃO: concluiu-se pela necessidade de realização de atividades participativas de educação em saúde, de modo a conduzir os adolescentes à crítica e reflexão tanto sobre o envelhecimento como sobre a condição do velho na sociedade contemporânea.